A mold for mitral valve reconstruction - Tan, Kai Yang (2018)
This project focused on the issues faced during the process of mitral heart valve reconstruction using the Mimics software. Mitral valve could be designed with ease and could easily be implemented in the medical industry in the future. The mitral valve plays an important role in the heart. It will weaken and deteriorate as the human body grows to age. Due to the advancement in medical innovations and smart technology it is possible to utilize the current technologies such as 3D printing as well as Computerized Aided Design software to aid in the reconstruction of a mitral valve. The Mitral valve disease refers to defects of the mitral valve. This valve is located at the left ventricle of the heart. The function is to make sure blood flowing in single direction from the left atrium to the left ventricle and prevents it from flowing backward. When the mitral valve fails to work properly, heart is unable to pump enough blood out of the left ventricular chamber to supply the body with sufficient oxygen-filled blood. If the valve is left untreated, it can lead to heart failure or irregular heartbeats. This project focused on the design of the conduit. With the aid of Mimics software and CT scanning of the heart, reconstructed images were obtained and Mimics software was used to reconstruct a 3D model of the mitral valve as accurately as possible.